PERAN MEDIASI MOTIVASI KERJA PADA PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Ratna Andriya Ulfah; Didik Subiyanto; Ignatius Soni Kurniawan (Universitas Ahmad Dahlan, 2020)
This study aims to examine the effect of transactional leadership style and compensation on employee performance mediated by work motivation on the employees of the Sleman Regency. Sampling in this study uses probability method because the population of employees in the Regional Water Supply Company (PDAM) Sleman Regency is quite a lot to be studied. Data collection techniques using a questionnaire distributed by the Director of PDAM Sleman. Data analysis techniques using the application SPSS version 21 include validity test, reliability test, descriptive statistics, classic assumption test, multiple linear regression test, hypothesis test, and coefficient of determination. The results of this study indicate that the transactional leadership style variable has a positive and significant effect on work motivation, compensation has a positive and significant effect on work motivation, transactional leadership has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, transactional leadership has a positive and significant effect on employee performance mediated by motivation, compensation has a positive and significant effect on employee performance mediated by motivation. The most dominant influence is work motivation variable, then compensation variable is followed